2018
DOI: 10.1177/0309132518778220
|View full text |Cite
|
Sign up to set email alerts
|

Rural geography III: Marketing, mobilities, measurement and metanarratives

Abstract: This report focuses on the individual and collective capacities of rural people to develop innovative and entrepreneurial approaches to local development (e.g. via place marketing) and to create music, art, prose and other cultural forms in place which in themselves serve to promote rural localities and regions to non-local people. In addition, it considers people’s propensities to move to new places on a permanent or temporary basis, and how this mobility affects individuals and host and sending communities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Due to rural migration, new social groups are emerging in rural areas, which are identified with diverse social and economic practices and engaged with innovative and/or hybrid activities, and whose lifestyles differ significantly from that of local people ( Stockdale, 2006 ; Mahon, 2007 ; Stockdale, 2014a ). Despite the complexity and indeterminacy of the term, the factors connected to counter-urbanisation are open to multiple interpretations, allowing for the rethinking of the facts behind the phenomenon ( Argent, 2019 ). For example, counter-urbanisation may be the result of movements by former city dwellers who develop a genuine attachment to a rural place (or pro-rural counter-urbanisation see Halfacree and Rivera, 2012 ), or by urban dwellers who were driven away from the city by unemployment, the economic recession and so on.…”
Section: Theoretical Framing For Understanding Migrant Well-being In mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to rural migration, new social groups are emerging in rural areas, which are identified with diverse social and economic practices and engaged with innovative and/or hybrid activities, and whose lifestyles differ significantly from that of local people ( Stockdale, 2006 ; Mahon, 2007 ; Stockdale, 2014a ). Despite the complexity and indeterminacy of the term, the factors connected to counter-urbanisation are open to multiple interpretations, allowing for the rethinking of the facts behind the phenomenon ( Argent, 2019 ). For example, counter-urbanisation may be the result of movements by former city dwellers who develop a genuine attachment to a rural place (or pro-rural counter-urbanisation see Halfacree and Rivera, 2012 ), or by urban dwellers who were driven away from the city by unemployment, the economic recession and so on.…”
Section: Theoretical Framing For Understanding Migrant Well-being In mentioning
confidence: 99%
“…But there are also cases where there is multi-local living that primarily relates to better off socioeconomic groups. It is suggested that more targeted research is required to (re)connect mobilities, lifestyles and life-courses in rural areas ( Argent, 2019 : 762). Recent research has de-emphasized counter-urbanization as a comprehensive trend and sheds more light on the (inter)subjective and agency aspects of movements to/across rural areas ( Stockdale, 2014b ; Scott et al, 2017 ).…”
Section: Theoretical Framing For Understanding Migrant Well-being In mentioning
confidence: 99%
“…The tensions that private roads and private land caused came up in other interviews as well (e.g., Kätlin in the previous subchapter). Sirje said how the change of ownership of a common site for the yearly Midsummer night's party 4 eventually led to changing the party site, as the owner did not take care of the site and it turned inappropriate. However, the new site was also on private property:…”
Section: Social and Materials Borders Of Communitiesmentioning
confidence: 99%
“…Parallel to these developments in academic literature (see also a recent review by Argent ), in rural policy discourse in the UK, art has been frequently promoted as a tool for creating jobs, attracting visitors and supporting rural businesses (e.g., Arts Council England ). Formal policy statements make a specific commitment to support arts and culture in rural communities (e.g., Arts Council England ), given that rural areas demonstrate greater engagement with art, although funding for creative practices remains more limited compared to urban areas (Arts Council England ).…”
Section: Beyond Creativity: Research With Artmentioning
confidence: 99%